2019
DOI: 10.1002/1873-3468.13544
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification and diapause‐related functional characterization of a novel dual‐specificity kinase gene, MPKL, in Locusta migratoria

Abstract: Diapause is an important overwintering strategy enabling Locusta migratoria to survive under stressed conditions. We identified a novel dual‐specificity kinase gene that is differentially expressed between long and short day‐treated L. migratoria. To determine its function on photoperiodic diapause induction, we cloned the specific gene. Interestingly, phylogenetic analysis shows that this dual‐specificity kinase is of the mycetozoa protein kinase‐like (MPKL) type and may have been transferred horizontally fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…Various aspects of the mechanism via which overwintering insects survive low temperature conditions have been studied (Rinehart et al, 2007; Clark and Worland, 2008;Fu et al, 2019;Hao et al, 2019). Insects enhance their cold resistance by means of behavioral, biochemical, and physiological strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Various aspects of the mechanism via which overwintering insects survive low temperature conditions have been studied (Rinehart et al, 2007; Clark and Worland, 2008;Fu et al, 2019;Hao et al, 2019). Insects enhance their cold resistance by means of behavioral, biochemical, and physiological strategies.…”
Section: Introductionmentioning
confidence: 99%
“…In the honeybee ( Apis mellifera ), phosphoproteomic analysis has been widely applied to assess the transition from nurse to forager bee, the embryo–larva transition, the production of royal jelly and venom, and the development of the salivary glands and hypopharyngeal glands [ 15 , 16 , 17 , 18 , 19 , 20 ]. Previous studies have demonstrated that phosphorylation modifications also participate in the regulation of insect diapause [ 21 , 22 , 23 , 24 , 25 ]. A prior report showed significant differences in 23 phosphoproteins in the brain of the cotton bollworm ( Helicoverpa armigera ) in the nondiapause- and diapause-destined pupae [ 26 ].…”
Section: Introductionmentioning
confidence: 99%